2022
DOI: 10.1021/acs.orglett.1c04146
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Conversion of Double Isocyanides with Alkenyl Bromide to Polysubstituted Pyrroles and 4-Imino-4,5-dihydropyrrolo[3,4-b]pyrrol-6(1H)-one Derivatives by Pd-Catalyzed Tandem Cyclization Reactions

Abstract: Herein a novel and concise approach to pyrrole skeletons via Pd-catalyzed tandem cyclization reactions is investigated. The substrates for the transformation could be readily prepared by phosphoric acid-catalyzed Ugi reactions with available starting materials. In this strategy, two isocyanides participate in sequential isocyanide insertion reactions, and the chemoselectivity of the products is regulated by the steric hindrance of the isocyanide. A plausible mechanism for the formation of the corresponding add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Meanwhile, the reaction of benzyl isocyanide 2a with a palladium complex to form intermediate D, then attacked by water molecules as nucleophiles to give E with the release of HCl. 15 Subsequently,…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Meanwhile, the reaction of benzyl isocyanide 2a with a palladium complex to form intermediate D, then attacked by water molecules as nucleophiles to give E with the release of HCl. 15 Subsequently,…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…). [27] The results showed that steric hindrance of substituents on nitrogen atom (R 3 ) in alkenyl bromides 54 have an influence on the reaction chemoselectivity and leads to the formation of different products. Accordingly, the reaction of isocyanides 2 and substrates containing R 3 with high steric hindrance (R 3 = t Bu and Ad) gave polysubstituted pyrroles 60 as products in moderate to good yields (58-83%) under aforementioned conditions.…”
Section: Alkynyl Aromaticsmentioning
confidence: 99%
“…As discussed (see Section 2 1,. Scheme 15), the transformation of unsaturated 2‐amino‐3‐bromocarboxamides with isocyanides induced by Pd(OAc) 2 and ligand L 6 , led to the formation of polysubstituted pyrroles with starting materials bearing bulky R 3 substituents [27] . Unexpectedly, however, alkenyl bromides with non‐bulky R 3 groups (Bu, Bn, Cy) participated in another route leading to condensed derivatives 33 with similar efficacy (Scheme 114).…”
Section: Condensed Bicyclic Moleculesmentioning
confidence: 99%
“…He, Wang, and co‐workers reported the synthesis of polysubstituted pyrroles via the conversion of alkenyl bromides and isocyanides with the use of Pd(OAc) 2 and 1,4‐bis(diphenylphosphano)butane (dppb) as ligand (L 6 ) [27] . Pyrrole derivatives were formed in tandem reactions with excess amount of isocyanides taking part in ring formation with their steric hindrance contributing to chemoselectivity (Scheme 15).…”
Section: Formation Of Monocyclesmentioning
confidence: 99%